The Influence of Brand Equity and Product Quality on Cimory Yoghurt Squeeze Purchase Decisions in Koto Tangah District, Padang City - Adha, Howardi Visza; Hendri, Muhammad Syahril (Adpebi Science Series, 2024)
This study aims to find out how the variables of Brand Equity and Product Quality affect the purchase decision of cimory yoghurt squeeze in Koto Tangah Padang District. The type of data used in this study is quantitative in the form of questionnaires from cimory consumers in Koto Tangah District. The population used in this study is all cimory consumers in Padang City. The results of the t-test showed that Brand Equity and Product Quality had a positive and significant effect on the decision to purchase cimory yoghurt squeeze in Koto Tangah Padang District with a t-value calculated for Brand Equity with a t-value of 5,503>t table 1,661 and a sig value of 0.000< 0.05 and Product Quality with a t-valueof 2,558> ttable 1.661 and a sig value of 0.012<0.05 with df 96-3 = 93, then the table t of 1.661 is obtained. The results of the F-test showed that the variables of Brand Equity and Product Quality together had a positiveand significant effect on the decision to purchase cimory yoghurt squeeze in Koto Tangah Padang District with the results of the F test knowing that fcalculated 29,237 > from ftable 3.09 and the significance of f = 0.000 was less than 0.05. From the results of the determinant coefficient analysis, the R Adjusted Square (R2) value was obtained of 0.386, which means that 38.6% of the variables of purchase decisions can be explained by the variables Brand Equity and Product Quality, while the rest (61.4%) can be explained by other variables that are not examined in this study.